Milking Reactivity in Primiparous Saanen Goats During Early Lactation: Effects on Milk Yield, Milk Quality and Plasma Cortisol Concentration - Andrioli, Mayara [UNESP]; Grajales-Cedeño, Joseph K. [UNESP]; Sant’Anna, Aline C. [UNESP]; Negrão, João A.; Paranhos da Costa, Mateus J. R. [UNESP] (MDPI, 2024)
The reactivity of primiparous goats during milking can significantly affect animal welfare and performance. The aim of this study was to investigate the progression of milking reactivity during lactation and its effects at early lactation on milk yield, milk quality, and plasma cortisol concentration in primiparous Saanen goats. The milking reactivity of 31 primiparous Saanen goats was evaluated on days 10, 30, and 60 of the lactation period by scoring step-kick behavior (SK) and head, ear, and tail movements (MOV). Milk yield, milk protein and fat percentages, somatic cell count (SCC), and plasma cortisol concentration were measured on day 10 of lactation. Goats’ milking reactivity was classified as low or high (according to the SK and MOV scores measured on day 10 of lactation). SK and MOV scores decreased over the lactation period, indicating that the goats habituated to the milking procedures. Milking reactivity only affected milk fat percentage, with the less reactive goats having more milk fat than the highly reactive ones. There was no evidence of stress when goats were subjected to milking procedures during early lactation. Further studies are needed to clarify the relationships of milking reactivity with stress response and their effects on milk yield and quality.
Keywords: cortisol; milk fat; milk protein; somatic cell count; temperament